2018
DOI: 10.1155/2018/6750264
|View full text |Cite|
|
Sign up to set email alerts
|

A Rare Presentation of Cardiac Tamponade from Metastatic Urothelial Carcinoma of the Bladder

Abstract: A 62-year-old man presented with 2 weeks of progressive dyspnea and chest pain. He was previously diagnosed with high-grade invasive urothelial carcinoma (UC) of the bladder and underwent neoadjuvant chemotherapy followed by radical cystectomy 10 months earlier, resulting in pathologic complete remission. Clinical evaluation and echocardiographic imaging was consistent with a diagnosis of cardiac tamponade. Due to a history of malignancy, the patient was referred for a surgical pericardial window, to include b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The analysis of 20 studies, plus our case report totaled 30 patients described between 1934 and 2023, proving the rarity of cardiac metastasis of TCC [ 2 , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ]. Data in showed that patients with cardiac metastasis from TCC are predominantly men (77.78 %), mean age 65.47 years, most patients were diagnosed after death by autopsy (57.90 %) ( Table 1 and Fig.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The analysis of 20 studies, plus our case report totaled 30 patients described between 1934 and 2023, proving the rarity of cardiac metastasis of TCC [ 2 , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ]. Data in showed that patients with cardiac metastasis from TCC are predominantly men (77.78 %), mean age 65.47 years, most patients were diagnosed after death by autopsy (57.90 %) ( Table 1 and Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Most diagnoses occurred with the aid of cystoscopy and transurethral resection. 18 studies [ 2 , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ]reported some type of treatment administered after a diagnosis of TCC, most patients were treated with radical cystectomy (50.00 %), chemotherapy (neoadjuvant or adjuvant) (44.45 %), and bladder reconstruction or urinary diversion (33.34 %) ( Table 1 ).
Fig.
…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our literature review, we found that cardiac metastasis from renal cancer (encompassing all histological subtypes) have been reported to be intra-atrium [ 9 , 10 ], intra-ventricular [ 11 , 12 ], myocardial [ 13 , 14 ], endocardial [ 9 ], pericardial [ 15 , 16 ], or involving multiple regions of the heart [ 9 , 14 ]. Cardiac metastasis can be asymptomatic or can present with life-threatening complications such as tamponade, outflow tract obstruction, arrhythmias, or valvular dysfunction [ 16 18 ]. Apart from routine transthoracic echocardiography, further imaging such as contrast-enhanced ultrasound, cardiac CT, cardiac MRI, or PET CT scan can be performed for further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…In the article titled “A Rare Presentation of Cardiac Tamponade from Metastatic Urothelial Carcinoma of the Bladder” [1], Dr. Amrou Abdelkader was missing from the authors' list. Dr. Amrou Abdelkader was involved in writing and editing the pathology portion of the article and providing the pathology photos (Figures 3(a)–3(d)) and the associated legend.…”
mentioning
confidence: 99%